The Timber Press guide to succulent plants of the world : a comprehensive reference to more than 2000 species - Dortort, Fred (Timber Press, 2011)
This encyclopedic yet accessible volume features comprehensive, richly illustrated descriptions of more than 2000 succulents, including both familiar species as well as less common, more exotic plants